FuzSy: Um Escalonador baseado em Qualidade de Serviço e Lógica Fuzzy - Souza, Fabrício R. de; Figueiredo, Fátima Duarte (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
In this paper, FuzSy, or Fuzzy Scheduler, is presented. It is a cellular network packet scheduler. It is based on quality of service and fuzzy logic. Classic solutions utilize static packet scheduling, following a prearranged priority order. Static scheduling can be unfair, or waste network resources, trying to allocate resources. FuzSy utilizes metadata from the network and, from choices made by the fuzzy logic mechanism, which seeks to prioritize classes that have a higher risk of not reaching it's QoS requirements, sets a dynamic packet priority. This priority is said to be dynamic because, is one class is in a QoS position that is not favorable, the scheduler set this class' priority to be higher, regardless of any previous set priority. Fourth generation, 4G, network simulations were conducted. The results show that FuzSy was able to keep all QoS within 3GPP stipulated values and was able to achieve higher fairness, not benefiting any class at other's cost. One of FuzSy's advantages, in relation to the other schedulers, cited in this paper, is that parameters can be added to or deleted from the fuzzy mechanism. With that, on specific situations such as places hosting large scale events the scheduler can be altered and utilize different parameters and rules to better serve the users.